2021
DOI: 10.1093/ptj/pzab041
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Learning–Based, Fully Automated Program to Segment and Quantify Major Spinal Components on Axial Lumbar Spine Magnetic Resonance Images

Abstract: Objective The paraspinal muscles have been extensively studied on axial lumbar magnetic resonance imaging (MRIs) for better understanding of back pain; however, the acquisition of measurements mainly relies on manual segmentation, which is time consuming. The study objective was to develop and validate a deep-learning–based program for automated acquisition of quantitative measurements for major lumbar spine components on axial lumbar MRIs, the paraspinal muscles in particular. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…Xia and colleagues [11] tested several network architectures, including the U-Net as well as novel solutions, to segment psoas major, erector spinae, and multifidus, obtaining excellent Dice similarity scores between 0.913 and 0.95 for the best-performing neural network. Other studies achieved relatively lower performances [21], or focused on different imaging modalities or fields of view [22,23]. In general, it can be concluded that our model achieved state-of-the-art performance and is the only one that has been externally validated on a purposely created dataset so far.…”
Section: Discussionmentioning
confidence: 68%
“…Xia and colleagues [11] tested several network architectures, including the U-Net as well as novel solutions, to segment psoas major, erector spinae, and multifidus, obtaining excellent Dice similarity scores between 0.913 and 0.95 for the best-performing neural network. Other studies achieved relatively lower performances [21], or focused on different imaging modalities or fields of view [22,23]. In general, it can be concluded that our model achieved state-of-the-art performance and is the only one that has been externally validated on a purposely created dataset so far.…”
Section: Discussionmentioning
confidence: 68%
“…This study demonstrated the possibility to extract accurate information about soft tissues from spine CT without the necessity to order an MRI, which is often expensive and time-consuming. Other studies have also shown the possibility to automatically calculate the spinal canal area [73] as well as segmenting and reconstructing multiple structures at the same time [47,66,72,75,79] with an elevate degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [71] exploited a BSU-net for IVDs segmentation on 20 MRI from the SpineWeb dataset, achieving a DICE of 89.4%. Shen et al [72] used a Feedforward NN on MRI of 120 subjects, achieving a Jaccard index for the segmentation of IVDs, spinal canal and muscles of 87, 82 and 85%, respectively. Gaonkar et al [73] applied a U-net to segment IVDs on 39295 MRI images, achieving an 88% DICE; they also combined an SVM with a Regression Tree to segment the spinal canal with a DICE of 87%.…”
Section: Deep Learningmentioning
confidence: 99%
“…The CNN markedly improved the efficiency of the segmentation, reducing the processing time from 20 min per image to only seconds. In addition to our work, CNN's have been used to automate the segmentation of the lumbar paraspinal and iliopsoas muscles from T 1 -weighted and Dixon MRI scans, respectively 25,26 . CNN's have also been applied to other spinal structures, allowing for the automatic quantification of vertebrae and intervertebral disc morphology from MRI 27 .…”
Section: Trmentioning
confidence: 99%